(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2022)
The Mallotus philippinensis Muell. Arg (MP, Euphorbiaceae) In tropical and subtropical parts ofthe outer Himalayas, is a widely spread perennial shrub or small tree. Since then, a variety of medicalbenefits of Mallotus philippinensis have been shown. The purpose of the current investigation was toascertain if fruit extract has the ability to heal wounds in rat models.